Four new species and new records of Veraphis Casey in Japan (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2019)
Four new species of the eutheiine genus Veraphis Casey are described, all based on specimens collected in Japan: V. loebli sp. n., V. mutsuensis sp. n., V. aomoriensis sp. n., and V. sakaii sp. n. New findings increase the number of Japanese Veraphis species to fourteen, and Japan becomes a country that houses the greatest known diversity of this rarely collected genus. The grammatical gender of Veraphis is identified as feminine, and species names previously treated as masculine are corrected accordingly. The distribution of all Veraphis species in Japan is summarized.